Transformasi Digital UMKM melalui Pelatihan Keterampilan Teknologi di Era Society 5.0 - Adi Lukman Hakim; Erna Nur Faizah; Rizky Wahyudha Rosiawan; Rudi Wibowo; Silvia Dwi Indriana; Aisy Faaikoh (Universitas Mataram, 2026)
This Technology skills training programs for Micro, Small, and Medium Enterprises (MSMEs) represent a strategic effort to strengthen business owners’ readiness to face digital transformation in the Society 5.0 era. This study aims to describe the practical impact of such training on enhancing the digital capabilities of MSMEs through a cross-sectoral survey approach. The findings indicate that the training has a positive impact on improving operational efficiency, particularly in inventory management and work processes, which have become more structured and effective. Additionally, the training facilitates market expansion through the use of digital platforms and e-commerce, enabling MSMEs to reach a broader consumer base. The shift toward online services has also enhanced the ability of SMEs to respond to consumer behavior that increasingly prioritizes the convenience of digital transactions. On the other hand, the integration of digital payment systems improves transaction efficiency and boosts customer trust in SME services. Strengthening brand and reputation through social media is another significant impact, marked by increased customer interaction and engagement in building the business’s image. Overall, the results of this study indicate that technological literacy plays a crucial role as a key factor in enhancing the competitiveness, efficiency, and sustainability of SMEs amidst the ever-evolving dynamics of the digital business landscape